2021
DOI: 10.3389/fphar.2021.725136
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Induces Apoptosis and Perturbs Mitochondrial Function in Human and Canine Glioma Cells

Abstract: Cannabidiol (CBD), the major non-psychoactive compound found in cannabis, is frequently used both as a nutraceutical and therapeutic. Despite anecdotal evidence as an anticancer agent, little is known about the effect CBD has on cancer cells. Given the intractability and poor prognoses of brain cancers in human and veterinary medicine, we sought to characterize the in vitro cytotoxicity of CBD on human and canine gliomas. Glioma cells treated with CBD showed a range of cytotoxicity from 4.9 to 8.2 μg/ml; canin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…This result effectively explains the phenomenon of the high-risk population having a higher immune infiltration score and a poorer prognosis. Although previous experimental research revealed that necroptosis kills cancer cells and exerts antitumor effects in glioma ( 37 40 ), necroptosis did not improve the glioma patients’ prognosis and some research showed that necroptosis-related genes were unfavorable prognostic markers in gliomas ( 26 , 41 ). We believed that necroptosis exerted an anti-tumor effect to promote glioma cells’ death, conversely, tumor cells released a variety of immunosuppressive cytokines and chemokines and necrotic tumor cells also attracted a variety of immune cells infiltrating.…”
Section: Discussionmentioning
confidence: 99%
“…This result effectively explains the phenomenon of the high-risk population having a higher immune infiltration score and a poorer prognosis. Although previous experimental research revealed that necroptosis kills cancer cells and exerts antitumor effects in glioma ( 37 40 ), necroptosis did not improve the glioma patients’ prognosis and some research showed that necroptosis-related genes were unfavorable prognostic markers in gliomas ( 26 , 41 ). We believed that necroptosis exerted an anti-tumor effect to promote glioma cells’ death, conversely, tumor cells released a variety of immunosuppressive cytokines and chemokines and necrotic tumor cells also attracted a variety of immune cells infiltrating.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the same factor may act in a pro-apoptotic way in one case, while in another the action may be anti-apoptotic. This situation applies, inter alia, to cannabinoids that induce apoptosis in some cases and act cytoprotectively in others [ 33 , 34 , 35 ]. It is believed that this may be due to the different expression of the receptors as well as the different activities of enzymes and regulatory proteins in different cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, exocannabinoids are believed to be potential medicinal agents used in the therapy of diseases in which apoptosis is dysregulated. Still, both endo- and exocannabinoids may act in a pro- or an anti-apoptotic manner, depending on the targeted cells [ 33 , 34 , 35 ]. It is believed that this may be due to the different expression of receptors as well as the different activities of enzymes such as COX-2 and the regulatory proteins in different cells.…”
Section: Discussionmentioning
confidence: 99%
“…The highest number of in vitro studies have been performed on tumour cells of the nervous system, followed by tests on breast cancer cell lines. IC 50 values of pure CBD varied widely from about 0.6 µM to more than 22 µM for tumours of the nervous system, and were more effective than CBD-E, THC or CBG [15][16][17][18][19][20]. In ependymoma cell lines, CBD and THC were similarly effective, whereas CBD was more potent in medulloblastoma [20].…”
Section: In Vitro Antitumour Potency Of Pure Isolated Phytocannabinoidsmentioning
confidence: 99%
“…Even small differences in the composition can have a pronounced impact on cytotoxicity. A recent study compared pure CBD (>99.9%) with almost pure CBD-E (96%) and found that all four glioma cell lines tested (two human glioma cell lines U87MG and U373MG; two canine glioma cell lines J3TBG and SDT3G) were marginally more sensitive to pure herbal CBD than to CBD-E [15].…”
Section: In Vitro Cannabidiol (Cbd) Was Often Morementioning
confidence: 99%